A Workshop on How to Find Current Topics For Research - Yustinus Calvin Gai Mali (Universitas Mathla'ul Anwar Banten, 2022)
Conducted in a 2-hour online workshop session format in November 2021, this community service program aims to share my practical experiences as an Indonesian researcher on finding current research topics, specifically in English as a Foreign Language (EFL) teaching and learning. The participants of this online workshop were seventeen (17) lecturers in the English Language Education program at Universitas Muhammadiyah Yogyakarta, Indonesia. Conducted synchronously in a Zoom platform, the workshop started with my presentation on three main points: (1) “my ways” in finding research topics, (2) my published articles that might provide writing ideas for the participants, and (3) reasons why the participants need to write and publish their work in an academic journal. This presentation session was ended by a question and answer session from the participants. Some reflective questions for Indonesian researchers and ideas for future community service programs were also presented.